Cultural management and heritage built in an urban context. Case study: “Huaca Huantille Archaeological Site”. Lima-Peru (1982-2012) - Centurión Cancino, Evelyn (2020)
For many decades, the archeological sites in the urban environment of Lima have suffered constant damages, from its illegal occupation, alteration, predation, illicit digging, among others; being most of them part of the historical memory and training of the citizens in their cultural identity, each time archeological information is detached from them, which should be diffused in order to strengthen cultural policies promoted by the State to ensure its protection. It is in this regard this article comprises a case study of the archeological site Huaca Huantille, located in the district of Magdalena del Mar, Lima; where strenuous efforts are made for its restoration, investigation and conservation as built cultural heritage that is circumscribed within an urban environment, and in which it is urgent that a new management proposal is planned for its use and advantage as a resource and source of knowledge for the citizen; whose main element is the environment where it is circumscribed and a certain social group with different traditions, beliefs and principles concerning itself has been currently consolidated.